Impact of an enhanced recovery program for cesarean delivery on postoperative opioid use. (August 2020) - Lester, S.A.; Kim, B.; Tubinis, M.D.; Morgan, C.J.; Powell, M.F.
Highlights: Cesarean delivery patients in the enhanced recovery program received fewer opioids. Average pain scores remained mild despite the reduced opioid consumption. Fewer than half the patients required an opioid within 24 h of discharge. Early oral intake was not associated with increased anti-emetic requirements. Abstract: Background: Cesarean delivery is one of the most common surgeries performed worldwide and the adoption of enhanced recovery programs for cesarean delivery is gaining popularity. We tested the hypothesis that implementation of an enhanced recovery program for cesarean delivery would be associated with a decrease in postoperative opioid consumption. Methods: We compared a retrospective cohort of women delivered by elective cesarean delivery (January 1, 2017 to June 30, 2018) to a prospective cohort exposed to the enhanced recovery protocol (July 1, 2018 to December 31, 2018). The primary outcome was inpatient maternal opioid use, measured as total oral morphine equivalents. Secondary outcomes included postoperative 0–10 pain scores, length of stay, 30-day postoperative complication rates, and hospital re-admissions. Results: Data from 541 patients were analyzed. The enhanced recovery cohort used significantly less oral morphine equivalents compared with the pre-enhanced recovery cohort (60.3 mg vs 104.3 mg, P <0.001). The number of patients who required opioid medication within 24 h of discharge was significantly reduced in the enhanced recovery cohort (41.1% vs 74.6%, P <0.001). There were no significant differences in average pain scores (1.6 vs 1.9, P =0.037). Conclusions: The implementation of an enhanced recovery program for cesarean delivery was associated with a significant reduction in postoperative opioid consumption throughout hospitalization, with average pain scores remaining <2. Implementation of this program was also associated with an increase in the number of patients who were opioid-free 24 h prior to discharge.